A CONTRIBUTION TO THE ANOMALIES OF THE ARM FLEXORS - Machalek, Libor; Holibkova, Alzbeta; Charamza, Jiri; Cach, Alexandr; Holibka, Radomir (Biomedical papers, 1998)
The authors described a unique occurence of the third head of the biceps brachii, pointing out the possibility of attachementof its muscle bundles after partial rupture. This situation could occur, especially when this anomaly was found onlyunilaterally.Dedicated to the 65th anniversary of Doc. MUDr. et RNDr. Milan Cerny, CSc.
Keywords: Arm flexors / Biceps brachii /Muscles anomalies